Structural and techno-functional properties of bovine collagen and its application in hamburgers - Alexandretti, Christian (Array, 2019)
The objective of this work is to characterize two types of bovine collagen (fibre and powder), evaluating its application in mixed hamburger formulations, as well as the quality characteristics of the products. The collagen fibre had a fibrillar structure, molecular mass 100 kDa and greater gel strength (146 315 Pa) and protein content (97.81 %) than the powdered collagen, which had molecular mass from 50 to 100 kDa, greater hydroxyproline content, and a morphological structure with spherical microparticles more amorphous than the collagen fibre. In this study we found that the addition of 1.5 % powdered collagen and 2.5 % flocculated soybean flour and/or 0.75 % powdered collagen and 3.5 % flocculated soybean flour did not deteriorate the technological properties or the sensory attributes of hamburgers. The use of collagen is a promising alternative, since it has functional properties, improves the texture characteristics of a product, and is of low cost.